Phylogeny of Adramini (Diptera, Tephritidae) based on integrative evidence. (18th October 2020) - Chen, Xiaolin; Freidberg, Amnon; Islam, Md Sajedul; Zhu, Chaodong
Abstract: Species of the tribe Adramini (Tephritidae: Trypetinae) are usually slender, and some specific species have eyes borne at the ends of their long stalks. This tribe is mainly distributed in the tropics and subtropics of the Afrotropical, Oriental and Australasian Regions; relatively few species occur in the Palearctic and Nearctic Regions. The phylogeny of the tribe Adramini is presented here based on analysis of morphological and molecular information (DNA sequences of nuclear 28S rDNA, mitochondrial COI and COII, and 16S rDNA genes) for its representative species in most genera. Three monophyletic groups (Adrama‐com‐group, Pelmatops‐com‐group and Dimeringophrys‐com‐group) were discovered in the combined morphological and molecular tree. The results showed moderate support for the monophyly of Adramini and strong support for most of its genera. However, Euphranta appears to be polyphyletic. Sapadrama, Celidodacus and Euphranta are basal taxon, and Coelopacidia, Soita and Trypanophion are closely related to the stalk‐eyed fruit flies ( Pelmatops  +  Pseudopelmatops ). A hypothesis regarding the morphology–function relationships for two main groups of Adramini (Adrama‐group and Pelmatops‐group) with different evolving probabilities is inferred. Sapadrama is proposed be removed from Adramini; a new genus, Ichneumonomacula Chen gen. n. and a new species Ichneumonmacula wangyongi Chen sp. n., are recognized and described, and a key to recognize the genera of Adramini around the world is provided.